The effectiveness of brain-based learning model (BBL) integrated with the whole brain teaching (WBT) model toward students’ retention - Baiq Sri Handayani; Nining Purwati (Biosfer: Jurnal Pendidikan Biologi, 2022)
Retention of learning results is a measurement of students’ ability to remember the lesson being learned after an amount of time before. This research aimed at investigating the effectiveness of the Brain-Based Learning Model (BBL) integrated with the Whole Brain Teaching (WBT) model on the retention of students’ learning results. This research was a quasi-experiment using a posttest-only control group design. The population of this research was the students of State Junior High Schools in Malang in the 2017/2018 academic year. The samples were selected from State Junior High School 1, State Junior High School 4, State Junior high School 6, State Junior High School 8, State Junior High School 15, State Junior High School 17, Junior high school 25, and Junior High School 26. The results of the data analysis showed that the learning model provides a significant effect on the retention of students’ science learning in Junior High schools in Malang. LSD notation shows that the effect of the WBT model integrated BBL model on student learning retention is lower as much as 6,79% and significantly different compared to the WBT model. The effect of that model is significantly different from the effect of BBL learning but higher as much as 8,06% and significantly different compared to the effect of the BBL learning model as well as higher (14,12%) and significantly different compared to the effect of conventional learning.